The ANTIBIOTIC CONSUMPTION AT A PEDIATRIC WARD AT A PUBLIC HOSPITAL IN INDONESIA - FAUNA HERAWATI; MUHAMAD SATRIA MANDALA PUA UPA; RIKA YULIA; RETNOSARI ANDRAJATI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The aims of the study are to describe how antibiotics were used in a pediatric ward and to observe how they were prescribed for infectious diarrheas of bacterial origin indication. Diarrhea or acute gastroenteritis is one of the most common infection diagnoses observed among the hospitalized children. Rehydration therapy is the key treatment for children with diarrhea. With the zinc supplement, the duration of the hospital stay can be reduced. Thus, the decision whether the local or regional health authorities need to provide an antibiotic treatment depends on the etiology of the disease, the patient’s nutritional history and immunological status, and eventually, the severity of the disease. Good anamneses and diagnoses are essential to decide whether antibiotic treatment is required. Methods: The observation in this study consists of two phases. The first-phase observation was taken from the diagnosis and the number of antibiotics used in 2016 retrospectively calculated from each of the patients’ medical records. Meanwhile, the second phase descriptive observation was prospectively drawn from the stool culture and the number of antibiotics prescribed to 21 inpatient diarrhea children between May 2017 and December 2017. The amount of antibiotic consumption was administered based on defined daily dose (DDD) and days of therapy (DOT). Results: In 2016, 56% (828/1476) of the patients received antibiotic prescriptions. On average, the DDD per 100 bed-days was 45.57. In the prospective study, six of 21 patients with diarrhea were prescribed antibiotics intravenously. The DOT was 3.5 days and the DDD for these patients was 12.10/100 bed-days. Conclusion: There was a high consumption rate of antibiotics which was not indicated in each patient’s etiology of diarrhea in the hospital during the period. Thus, the recommendation is to encourage health authorities to judiciously prescribe antibiotics according to the guidelines.